(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
In recent years, virtual wallets and neobanks have emerged, operating exclusively online. Currently, 70% of the Spanish population uses digital banking, with an expected increase of 6 million customers in the next 5 years. While it appears to be a favorable environment, only companies offering innovative and legally adaptable products will benefit. A significant Spanish bank is compelled to adopt new technologies to streamline processes and expand internationally. Functionality and the core banking system were analyzed using the MOGIT model for technological innovation management. The importance of tools such as BPM is emphasized, being crucial yet challenging to change for expansion and the development of new products. Weak managerial leadership has led to rework and a lack of coordination, hindering the implementation of new technologies to date.